1. Spirituality of Music as a Factor of (Self) Instruction and of (Self) Education of Personality - Gagim Ion (Sciendo, 2016)
The impetus for writing this article was the desire to "get to the bottom", to "disentangle the essence" of what music education in terms of exploring the depth, the sacred sense of the relationship "man-music", of the aspiration to examine this issue with the teacher's eyes - for all questions and all answers received contribute to the improvement of so-called education through music. In this article, the author expresses his position that, music education, by its essence, is far from the design made before, but in fact - far from the goal officially proclaimed. The music itself, as one of the most mysterious phenomena of this world. Its knowledge, its understanding, the assimilation and absorption of the cosmic and divine substance at the level of personal experience - this is music education in its highest sense. We consider them universal by nature and extent of aspects and levels of the spiritual, existential life of man in its deep forms. The author examines the experience acquired as a self-instruction (professionally) and self-education (personally) practice throughout life, in one of the highest areas of the human mind - in music. He had the chance to work especially in the field of music. He had the chance to experience music especially and he was able to devote his "self" to it.